2020
DOI: 10.3390/polym12061420
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Robust Superhydrophobic Surfaces with Dual-Curing Siloxane Resin and Controlled Dispersion of Nanoparticles

Abstract: We developed a simple method for the fabrication of superhydrophobic surfaces on various substrates using spray coating. The fabrication method started with the blending of a modified hydrophobic siloxane binder, silica nanoparticles, and a volatile solvent by sonication. The mixture was spray-coated on various surfaces such as slide glass, paper, metal and fabric, forming a rough surface comprising silica particles dispersed in a hydrophobic binder. Surface hydrophobicity was affected by the surface energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…SEM image of the pristine SSM is shown in Figure 2A. It can be seen that the surface of the unsprayed deposited pristine SSM is relatively smooth with a low surface roughness, which leads to a high surface energy 21 enhancing adsorption capacity of water. This is also demonstrated by the later water droplet contact experiments.…”
Section: Resultsmentioning
confidence: 99%
“…SEM image of the pristine SSM is shown in Figure 2A. It can be seen that the surface of the unsprayed deposited pristine SSM is relatively smooth with a low surface roughness, which leads to a high surface energy 21 enhancing adsorption capacity of water. This is also demonstrated by the later water droplet contact experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al prepared single layered antireflection (AR)-cum-hydrophobic coating onto fused silica glass using a hydroxy terminated PDMS silica ormosil system followed by curing at 160 1C. 20 Kim et al reported hydrophobic coating materials with functionalization of (hepta decafluoro-1, 1, 2, 2-tetrahydrodecyl) triethoxysilane (FAS) and epoxy in GLYMO using (3-aminopropyl) triethoxysilane (APTMS) followed by curing at 150 1C/2 h. 21 Nixon et al developed polysiloxane and acrylic polymer based ambient temperature curable coating composition and claimed that it can be used as a protective primer coating onto the structural component. However, in this work, the transparency, mechanical stability (hardness and modulus) and self-cleaning properties of the coatings have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although the coating approach is highly beneficial, a major problem is that the existing coating materials have low mechanical durability, flexibility, and stretchability under harsh chemical and physical conditions . There have been several attempts to achieve mechanically durable superhydrophobic surfaces using diverse bonding methods, such as commercial adhesives, chemical bonding, and physical interlocking , approaches. However, coating adhesives form a highly rigid layer on the substrate, which causes inevitable damage to the coating (e.g., cracking or detachment from the substrate) under vigorous motions, such as bending, twisting, and squeezing .…”
Section: Introductionmentioning
confidence: 99%